Flow-through anterolateral thigh flap for simultaneous soft tissue and long vascular gap reconstruction in extremity injuries: Anatomical study and case report - Kanit Sananpanich (2018)
47 dissections of cadaver thigh were studied to investigate pedicle configurations in the lateral descending branch of the lateral circumflex femoral arterial system, which can be used in harvesting a flow-through anterolateral thigh flap. The descending branch arose from the lateral circumflex femoral artery in 38 of the dissections, and the mean diameter at its origin was 3.0 mm (range, 2.2-4.0 mm). Skin peforators were of the solely musculocutaneous type in 37 dissections and were a combined septo-musculocutaneous type in 10 dissections. Pure septocutaneous perforator was not found in this study. During the descending branch's journey to the distal part of the thigh, several branches went into the vastus lateralis and vastus intermedius muscles. The diameters were tapering and the mean terminal diameter was 1.3 mm (range 0.9-1.8 mm), which required intraoperative judgment for proper matching of diameter of the flow-through pedicle and the recipient artery. The mean total length of the descending branch from its origin to terminus was 30.3 cm (range 22.5-37.1 cm). In four dissections, the descending branch could not be used as a flow-through anterolateral thigh flap because the origin of the perforator arose from the transverse branch. A flow-through anterolateral thigh flap has several advantages, including a large cutaneous area, acceptable donor-site morbidity, adjustable thickness, the ability to combine adjacent muscle or fascia lata and the possibility of simultaneous reconstruction of long arterial gap and soft-tissue defects. Four patients with severe injury and a vascular gap of longer than 10 cm in the extremities were used to confirm the usefulness of this application. © 2008.